GROUP DISCUSSION AND ICTS IN TEACHING AND LEARNING ENGLISH IN LARGE CLASSES - Puspita Dewi (Politeknik Negeri Bengkalis, 2019)
This study is concerned with Information Communication and Technologies (ICTs) and Group Discussion (GD) that become one of the most effective solutions to the problem. Universitas Bumigora has numerous students in one class in which each class consists of approximately 50-60 students. The aims of this study are to identify studentsâ€™ perspectives on GD and ICTs and to compare men's and womenâ€™s perspectives on GD and ICTs in large classes. This study was conducted in two big classes. The instrument in this research was a questionnaire. The questionnaire was used to get information about the studentsâ€™ responses to the application of FGD and ICTs in teaching and learning English and to identify the differences responses between man and women group. The data obtained were analyzed qualitatively and quantitatively. This study was conducted in two big classes. The instrument in this research was a questionnaire. The questionnaire was used to get information aboutthe studentsâ€™ responses to the application of FGD and ICTs in teaching and learning English. The data obtained were analyzed qualitatively and quantitatively. Based on the results, the students believed that group discussion and ICTs belong to â€œvery goodâ€ and â€œgoodâ€ with range score 3.11-3.44.